Influence of health resort treatment on the level of systemic inflammation in patients after new coronavirus infection - V. A. Beloglazov; L. Sh. Dudchenko; I. A. Yatskov; E. A. Solovyova; N. A. Shadchneva; S. N. Belyaeva; D. I. Ulyanova (Acta Biomedica Scientifica, 2023)
Background. Low-grade inflammation is currently one of the main risk factors for the development of adverse events in the cardiovascular system, including death from cardiovascular diseases or their complications that cause mortality in the postCOVID period.The aim of the study. To assess the impact of health resort treatment in the conditions of the Southern Coast of Crimea on clinical and functional parameters, as well as on the level of systemic inflammation in patients after a new coronavirus infection.Materials and methods. The study included 67 patients (54.9 ± 9.05 years) in the post-COVID period who underwent health resort treatment at the I.M. Sechenov Academic Research Institute of Physical Treatment Methods, Medical Climatology and Rehabilitation. Methods of health resort treatment included climatic treatment on the Southern Coast of Crimea, therapeutic breathing exercises, terrainkur, and various methods of respiratory therapy. In all patients, the study of the C-reactive protein (CRP) in peripheral blood upon admission and at discharge was carried out.Results. Despite a statistically significant improvement in most clinical and functional parameters, the level of CRP and the number of leukocytes and their subpopulations in peripheral blood in patients who underwent health resort treatment did not differ significantly (p > 0.05) from the baseline values obtained upon admission at the I.M. Sechenov Academic Research Institute of Physical Treatment Methods, Medical Climatology and Rehabilitation. The CRP index upon admission and at discharge corresponded to the lower limit of the interval specific for low-grade inflammation (from 3 to 10 mg/l).Conclusion. Our results indicate the lack of effectiveness of the presented plan of health resort treatment in the correction of low-intensity inflammation, as well as the necessity for deeper scientific research in the direction of studying the mechanisms of low-grade inflammation development and the methods of its management.